Frequency of Giardia duodenalis infection and its genetic variability in dogs in Cuiabá, Midwest Brazil - Yolanda Paim Arruda Trevisan; Arleana do Bom Parto Ferreira de Almeida; Luciano Nakazato; Thabata dos Anjos Pacheco; Jéssica Iglesias de Souza; Darlan Henrique Canei; Mariana Elisa Pereira; Maerle Oliveira Maia; Richard Campos Pacheco; Val´éria Régia Franco Sousa (Journal of Infection in Developing Countries)
Introduction: Giardia duodenalis, a unicellular, eukaryotic, and flagellated protozoan, presents two evolutionary forms in its life cycle, namely, trophozoites and cysts. It causes diarrhea in humans, dogs, cats, rodents, and ungulates. Despite being morphologically similar, the isolates of G. duodenalis are genetically diverse, affecting the stability and unanimity of taxonomic classification. Since different Giardia assemblages may occur within one isolate, multilocus genotyping is recommended for the genetic identification.